Real-Life Effectiveness of Vismodegib in Patients with Metastatic and Advanced Basal Cell Carcinoma: Characterization of Adverse Events and Assessment of Health-Related Quality of Life using the Dermatology Life Quality Index (DLQI) Test - Alessia Villani; Gabriella Fabbrocini; Milena Cappello; Claudia Costa; Massimiliano Scalvenzi (Adis, Springer Healthcare, 2019)
Abstract Introduction Non-melanoma skin cancer (NMSC) is the most common type of human tumor, with an estimated five million new cases each year. NMSC has been described as having a major impact on the health-related quality of life of the patient. Vismodegib is a hedgehog pathway inhibitor therapy for patients who are affected by locally advanced basal cell carcinoma (laBCC) and metastatic basal cell carcinoma and are ineligible for surgery and/or radiotherapy. The objective of this study was to assess treatment-emergent adverse events reported by patients with advanced BCC who were undergoing hedgehog pathway inhibitor therapy with vismodegib, and to quantify their health-related quality of life using the Dermatology Life Quality Index (DLQI) questionnaire. Methods Patients with advanced and/or multiple basal cell carcinomas treated with vismodegib at the Non-Melanoma Skin Cancer Unit of the University of Naples Federico II (Italy) were consecutively enrolled. Each patient was evaluated every month until the end of the treatment cycle to assess adverse events related to the drug and the patient's quality of life. Results 48 patients (35 males and 13 females) with advanced BCC were included in the study. Muscle spasms, alopecia, and dysgeusia were the most frequently reported adverse events. 41 patients completed the DLQI questionnaire at the baseline visit and after 6 months of treatment. The average reported DLQI score decreased from a mean value of 5.7 at the baseline visit to 0.4 after 6 months of treatment. Conclusion This is the first study to demonstrate a significant change in patient health-related quality of life from baseline to 6 months after hedgehog pathway inhibitor therapy initiation using the DLQI test. Interestingly, patients with BCC in visible areas such as the face or neck presented an overall DLQI score that was higher than that of patients with BCC located on the trunk and legs at the baseline visit, but the DLQI scores of these two groups were almost the same after 6 months of vismodegib therapy.